Aplikasi Model VRP dan Metode Saving Matrix untuk Mengoptimalkan Rute Pendistribusian Pupuk di CV. Al-Zaman - Koko Hermanto; Silvia Firda Utami; Wari Ammar Abdul Jabbar (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2021)
Determining the optimal route is very important in distribution of goods or services, because it can reduce costs and time. CV. Al-Zaman is a company that distributes urea fertilizer in Sumbawa Regency. So far, the company has never determined the shortest route in fertilizer distribution. This research will analyze the determination of the shortest route of distribution of fertilizer by CV. Al-Zaman, whose distribution route was previously modeled into the Vehicle Routing Problem (VRP) model, then the model was solved using the Saving Matrix method in determining the shortest route. So far, the distribution process is based on the driver's experience without analyzing the shortest route first. The distribution is carried out by 15 vehicle fleets with a capacity of 10 tons. The distribution process carried out by the vehicle fleet starts from the warehouse to all destination stores (vertex) and then returns to the warehouse. The results of the analysis using the Saving Matrix method and the VRP model resulted in savings of 75.1 km from the routes that have been used by the company. Keywords: Shortest Route, Distribution, Saving Matrix, VRP